Relationship between epithelial cell adhesion molecule (EpCAM) overexpression and gastric cancer patients: A systematic review and meta-analysis. - Meng Dai; Fei Yuan; Cuiqun Fu; Guodong Shen; Shilian Hu; Gan Shen (PLoS ONE)
Objectives The epithelial cell adhesion molecule (EpCAM) is one of the most commonly used markers of cancer stem cells (CSCs), but the clinical and prognostic significance of EpCAM in gastric cancer (GC) remains disputable. Motivated by heterogeneous and inconclusive results, we conducted a systematic review and meta-analysis to systematically summarize and elucidate the association between EpCAM overexpression and GC patients. Methods The PubMed, Cochrane Library, Medline, Web of Knowledge and the China National Knowledge Infrastructure (CNKI) databases were searched to identify relevant studies. The RevMan 5.3 software was used for the meta-analysis. Fixed-effects or random-effects models were applied depending on the presence of heterogeneity. The pooled odds ratio (ORs) and 95% confidence intervals (CIs) were applied to estimate the associations between EpCAM and gastric cancer. For the significant heterogeneity studies, sensitivity analyses were applied based on the population to test the robustness of the pooled results and identify possible sources of heterogeneity. Results A total of 11 studies including 1960 GC patients met our inclusion criteria. The results of the meta-analyses revealed that there were significant differences in EpCAM overexpression and tumour size (OR = 2.97, 95% CI: 2.13~4.13, P < 0.00001), the nature of the tissue (OR = 80.30, 95% CI: 29.21~220.81, P < 0.00001), lymph node metastasis (OR = 2.78, 95% CI: 1.23~6.27, P = 0.01), and the cumulative 5-year overall survival rate (OR = 0.54, 95% CI:0.29~0.99, P = 0.05). No significant associations were identified between EpCAM overexpression and gender (OR = 0.89, 95% CI: 0.66~1.19, P = 0.43), age (OR = 1.13, 95% CI: 0.58~2.20, P = 0.73), tumour stage (OR = 2.26, 95% CI: 0.79~6.45, P = 0.13), distant metastasis (OR = 2.15, 95% CI: 0.20~22.69, P = 0.52), TNM stage (OR = 5.14, 95% CI: 0.77~34.37, P = 0.09), Lauren type (OR = 1.18, 95% CI: 0.08~16.45, P = 0.9), differentiation (OR = 1.88, 95% CI: 0.65~5.41, P = 0.24). However, due to significant heterogeneity in tumor stage, lymph node metastasis, TNM stage, differentiation and Lauren type, these results should be taken carefully. Conclusions The meta-analysis demonstrated that the expression of EpCAM in the gastric cancer group was greater than that in the control group. Moreover, EpCAM overexpression was associated with larger tumour size, lymphnode metastasis and worse prognosis in gastric cancer. Due to significant heterogeneity, the sensitivity analysis suggests that population factor may be an important source of heterogeneity, and these results should be treated with caution. EpCAM may be useful as a novel prognostic factor, and large-scale and well-designed studies are needed to validate our results in the future.